Effect of cellulase adsorption on the surface and interfacial properties of cellulose - Dourado, Fernando (1999)
The surface properties of several purified cellulose (Sigmacell 101, Sigmacell 20, Avicel pH 101, andWhatman CF 11) were characterised, before and after cellulase adsorption. The following techniques were used: thin-layer wicking (except for the cellulose Whatman), thermogravimetry, and differential scanning calorimetry (for all of the above celluloses). The results obtained from the calorimetric assays were consistent with those obtained from thinlayer wicking – Sigmacell 101, a more amorphous cellulose, was the least hydrophobic of the analysed celluloses, and had the highest specific heat of dehydration. The other celluloses showed less affinity for water molecules, as assessed by the two independent techniques. The adsorption of protein did not affect the amount of water adsorbed by Sigmacell 101. However, this water was more strongly adsorbed, since it had a higher specific heat of dehydration. The more crystalline celluloses adsorbed a greater amount of water, which was also more strongly bound after the treatment with cellulases. This effect was more significant for Whatman CF-11. Also, the more crystalline celluloses became slightly hydrophilic, following protein adsorption, as assessed by thin-layer wicking. However, this technique is not reliable when used with cellulase treated celluloses.